THE CHALLENGES OF TEACHING INTERCULTURAL SKILLS - Kholova Shahnoza Davronovna; Narzulloyeva Nilufar Nazirjon qizi (Bright Mind Publishing, 2025)
In the context of globalization and increasingly active international interaction, the role of intercultural competence as an essential component of the educational process is increasing. This article examines the key problems of teaching intercultural skills: from methodological difficulties to psychological and pedagogical barriers. Special attention is paid to the specifics of teaching a foreign language as a means of intercultural communication and the need for a systematic approach to the formation of intercultural awareness in students.
Keywords: Intercultural skills, teaching problems, methodological difficulties, communication, translation, teaching methods.